2006
DOI: 10.1021/la061372+
|View full text |Cite
|
Sign up to set email alerts
|

Replica Molding of High-Aspect-Ratio Polymeric Nanopillar Arrays with High Fidelity

Abstract: Polymeric nanostructures with high aspect ratios, so-called nanopillars, are of interest for a wide range of applications. However, it remains a challenge to fabricate high-density, polymeric nanopillars using soft lithography when the feature size is decreased to hundreds of nanometers and the structures are close to each other. Here, we investigate the fidelity of replica molding technique to fabricate polymer nanopillar arrays with diameters ranging from 300 nm to 1 mum, and we compare the experimental resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
209
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(214 citation statements)
references
References 34 publications
3
209
0
1
Order By: Relevance
“…Anisotropic assemblies can also be obtained by the evaporation frontdirected method. This top-down/bottom-up hybrid strategy for preparing hierarchical structures features simplicity, scalability, and high flexibility in comparison with other state-of-the-art approaches such as photolithography (39), electron-beam lithography (20,40), and template replicating (4,16). Moreover, the assembled cells can be used as automatic microgrippers for selective trapping and controllable releasing of microobjects, suggesting numerous potential applications in the fields of chemistry, biomedicine, and microfluidic engineering.…”
Section: Selective Trapping and Releasing Of Microobjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anisotropic assemblies can also be obtained by the evaporation frontdirected method. This top-down/bottom-up hybrid strategy for preparing hierarchical structures features simplicity, scalability, and high flexibility in comparison with other state-of-the-art approaches such as photolithography (39), electron-beam lithography (20,40), and template replicating (4,16). Moreover, the assembled cells can be used as automatic microgrippers for selective trapping and controllable releasing of microobjects, suggesting numerous potential applications in the fields of chemistry, biomedicine, and microfluidic engineering.…”
Section: Selective Trapping and Releasing Of Microobjectsmentioning
confidence: 99%
“…When one aims to create slender structures, the dominant capillary force drives them to collapse, cluster, or be completely destroyed. Some efforts such as adopting a supercritical-point dryer (3,4) have been made to eliminate these unwanted behaviors when fabricating high-aspect-ratio structures. However, from another point of view, the capillary-driven bottom-up self-assembly can be exploited as a valuable tool to construct complex architectures.…”
mentioning
confidence: 99%
“…All of the patterned substrates were fabricated by replica molding from commercially available epoxy (D.E.R. 354; Dow Chemical) on glass slides, using poly(dimethylsiloxane) (PDMS) molds, following the procedure reported in the literature (50). Preparation of substrates with desired LC anchoring.…”
Section: -Nitro 14-benzenedicarboxylic Acid 14-bis[4-[(2-oxiranymentioning
confidence: 99%
“…However, only rod arrays with diameters larger than ∼500 nm (aspect ratios <50) have survived the drying process without complete collapse, as demonstrated in the scanning electron micrographs seen in Figure 2. Previous work 15,16 has shown that the collapse of similar structures with low Young's moduli and high aspect ratios is due to surface adhesive forces between neighboring structures (lateral collapse) or between the rod structures and the substrate (ground collapse). The aspect ratio at which structures become susceptible to collapse depends on the work of adhesion of the material, which in turn is a function of the medium surrounding the structures.…”
mentioning
confidence: 99%